Characterisation of a Bacterial Galactokinase with High Activity and Broad Substrate Tolerance for Chemoenzymatic Synthesis of 6‐Aminogalactose‐1‐Phosphate and Analogues. (4th January 2018) - Huang, Kun; Parmeggiani, Fabio; Pallister, Edward; Huang, Chuen‐Jiuan; Liu, Fang‐Fang; Li, Qian; Birmingham, William R.; Both, Peter; Thomas, Baptiste; Liu, Li; Voglmeir, Josef; Flitsch, Sabine L.
Abstract: Glycosyl phosphates are important intermediates in many metabolic pathways and are substrates for diverse carbohydrate‐active enzymes. Thus, there is a need to develop libraries of structurally similar analogues that can be used as selective chemical probes in glycomics. Here, we explore chemoenzymatic cascades for the fast generation of glycosyl phosphate libraries without protecting‐group strategies. The key enzyme is a new bacterial galactokinase (LgGalK) cloned from Leminorella grimontii, which was produced in Escherichia coli and shown to catalyse 1‐phosphorylation of galactose. LgGalK displayed a broad substrate tolerance, being able to catalyse the 1‐phosphorylation of a number of galactose analogues, including 3‐deoxy‐3‐fluorogalactose and 4‐deoxy‐4‐fluorogalactose, which were first reported to be substrates for wild‐type galactokinase. LgGalK and galactose oxidase variant M1 were combined in a one‐pot, two‐step system to synthesise 6‐oxogalactose‐1‐phosphate and 6‐oxo‐2‐fluorogalactose‐1‐phosphate, which were subsequently used to produce a panel of 30 substituted 6‐aminogalactose‐1‐phosphate derivatives by chemical reductive amination in a one‐pot, three‐step chemoenzymatic process. Abstract : Furnishing phosphates : A galactokinase from L. grimontii (LgGalK) has been identified and characterised; it shows broad substrate specificity towards different nucleotide phosphates and monosaccharides. This enzyme, in combination with a galactose oxidase variant was used in the chemoenzymatic synthesis of a panel of 6‐aminogalactose‐1‐phosphate analogues.